Pengembangan Media Pembelajaran Interaktif Berbasis Android Berbantukan Aplikasi SAC - Lutvia Hastari, Lutvia Hastari; Sari Saraswati (Cartesian: Jurnal Pendidikan Matematika, 2024)
Learning mathematics using a conventional learning model or teacher-centered learning system (teacher-centered learning), namely the lecture, discussion method and giving questions, can make students feel bored, they even tend to dislike the lesson and think that mathematics learning is very difficult and students tend to be passive. This research aims to develop Android-based media. In flat sided space building materials. The type of research used is the ADDIE model. Sampling used trials with large and small groups selected from different classes. The data collection techniques used are interviews, documentation, questionnaires and tests. The research data is in the form of values from expert validation results and from respondent questionnaires. The results of the research show that the media developed achieved an average percentage score of 83.38% with a very valid category. Meanwhile, the practicality of learning shows that the level of practicality is in the good category based on the percentage results of the average return value from teachers and students respectively at 79.77% and 79.33%. Apart from that, the effectiveness of learning media is obtained from student learning outcomes with complete class scores reaching 78.57%.